Inverse Kinematics With Closed Form Solution For Denso Robot Manipulator - Ikhsan Eka Prasetia; Trihastuti Agustinah (Jurnal Teknik ITS, 2015)
In this paper, the forward kinematics and inverse kinematics used on the Denso robot manipulator which has a 6-DOF. The forward kinematics will result in the desired position by end-effector, while inverse kinematics produce angel on each joint. Inverse kinematics problem are very difficult, therefor to obtain the solution of inverse kinematics using closed form solution with geometry approach. The simulation result obtained from forward kinematics and inverse kinematics is determining desired position by Denso robot manipulator. Forward kinematics produce the desired position by the end-effector. Inverse kinematics produce joint angle, where the inverse kinematics produce eight conditions obtained from closed form solution with geometry approach to reach the desired position by the end-effector.